β-Sitosterolemia and Xanthomatosis: A NEWLY DESCRIBED LIPID STORAGE DISEASE IN TWO SISTERS - Bhattacharyya, Ashim K. (1974)
Although the usual diet may contain 150-250 mg of plant sterols, chiefly β-sitosterol, only trace amounts of these sterols have heretofore been found in human or animal blood and tissues. We now report elevated plant sterol levels in the blood and tissues of two sisters with extensive tendon xanthomas but normal plasma cholesterol levels. Besides β-sitosterolemia and xanthomatosis, no other physical, mental, or biochemical abnormalities were detected. Repeatedly, the plasmas of the two sisters have contained 27.1 and 17.7 mg/100 ml of β-sitosterol, 9.7 and 8.2 mg/100 ml of campesterol, and 0.5 and 0.5 mg/100 ml of stigmasterol, respectively. These plant sterols constituted 15.6 and 11.3% of the total plasma sterols. Some 60% of the plasma β-sitosterol and campesterol was esterified; the measurable stigmasterol was entirely unesterified. The transport of the plasma β-sitosterol and campesterol was largely in low density lipoproteins (76 and 83%, respectively). High density lipoproteins carried the remainder. Plant sterols were barely detectable in the very low density lipoprotein fraction. Only trace amounts of stigmasterol could be detected in the low density and high density lipoprotein fractions. The plant sterol content of the red blood cells averaged 12-13 mg/100 ml packed cells or about 13% of the total sterols. Two tendon xanthoma biopsies with the usual high concentration of cholesterol had 36.7 and 4.0 mg of plant sterols/g dry wt, of which 25.7 and 2.9 mg were β-sitosterol, entirely in the free form. Plant sterols were also found in adipose tissue (0.2 mg/g wet wt) and in skin surface lipids (3.2 mg/g of lipid). The intestinal absorption of β-sitosterol in both the patients, measured by two techniques, indicated greatly increased absorption of this sterol (about 24 and 28% in the patients L. H. and R. H., respectively, normal absorption being <5%). We suggest that increased absorption of β-sitosterol must be considered as one cause of this disease. The reason for the extensive xanthomatosis in these two patients remains unknown. Perhaps in some way plant sterols initiated the development of xanthomas with otherwise normal plasma cholesterol levels. Clinical atherosclerosis has not yet occurred. The occurrence of β-sitosterolemia in these two sisters with un-affected parents suggests an inherited recessive trait.